Design for Emergency Management - van Manen, Saskia M.; Jaenichen, Claudine; Kremer, Klaus; Lin, Tingyi S.; Ramírez, Rodrigo (Design Research for Change, 2024)
Alpine Fault, Aotearoa, CARE package, DRM, EEW, Mexico City, NGO, NHC, New Zealand, The Bahamas, participatory design, pictogram, risk, signs, visual standards, wildfire, fire, flood, global warming, government, high-rise buildings, hurricane, hydrographs, industrial design, maps, opioid overdose